Bronze Statuettes in Roman Graves (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
This research follows the investigations about the relationship between bronze statuettes and contexts in Roman times, particularly explored by Annemarie Kaufmann-Heinimann. The rarity of bronze figures (human, divine and animals) in Roman tombs of Imperial age has been repeatedly emphasized. The aim of the paper is the collection, not exhaustive, of evidences in funerary contexts, to determine their meaning. From a methodological point of view, it was necessary to exclude figurines placed in graves but with other originary functions and several bronzes whose finding in tombs is unreliable. This preliminary survey has given about eighty all-round bronzes from burials, distributed in different areas, both in the Empire and marginal. Considering the huge amount of Roman burials known today, the overall evidence is scarce but allows some observations; it is evident the pre-eminence of Venus and Mercury, gods which had a funerary role. There is also an attempt to find the reasons of the rarity of metal statuettes in the tombs of roman period.
Keywords: statuettes; bronze; lead; roman graves